Does decompression surgery influence sagittal balance parameters in patients with lumbar spinal stenosis? - Joana Sofia Neves Leocádio (2022)
Purpose. The aim of this study was to investigate the effect that lumbar decompression surgery for lumbar spinal stenosis (LSS) has on sagittal balance parameters and its clinical significance. Methods. Observational registry-based cohort study for LSS degenerative cases treated with decompression surgery. Demographic and clinical data were collected, Core Outcome Measures Index (COMI) - back, EuroQoL (EQ-5D) and Oswestry Disability Index (ODI) questionnaires were used preoperatively and at 1 year follow-up. Pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), sagittal vertical axis (SVA) and Lumbar lordosis (LL) were measured before and 1 year after surgery. LL variation was the primary endpoint. Difference between real and ideal values were defined as relative lumbar lordosis and pelvic tilt (RLL and RPT). Unsupervised hierarchical clustering analysis (HC) was performed to identify subgroups with distinct patterns of variation. Results. A total of 95 patients were included, mean age of 63 years and 52.6% males, mostly 1-2 levels surgery (93.6%) and good or excellent outcome in 71.6%. The median difference between postoperative and preoperative LL was -1.3º (p=0.127), radiological parameters remained equivalent after surgery. Increased lumbar lordosis was correlated to ODI improvement (Pearson, r=-0.33, p=0.003), no other clinically significant correlations were found. Three clusters were identified after HC. Patients in cluster 2 (31.6% of patients) had decrease in LL after surgery (mean values for cluster 1, 2 and 3: 3.3o, -5.6o and 0.8o), increase in SVA (-5 mm, +25 mm and -19 mm) and no improvement in ODI (-23.1, 3.77 and -17.1). Conclusions. Lumbar decompression surgery has little effect in lumbar lordosis and sagittal balance. Cluster analysis yielded a subgroup of patients with worse outcomes, related to decrease of LL and increase of SVA after surgery.